1982
DOI: 10.1210/jcem-55-2-378
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Naloxone on Prolactin, Luteinizing Hormone, and Cortisol Responses to Surgical Stress in Humans

Abstract: To evaluate the possible involvement of endogenous opioid peptides in the responses of PRL, LH, and cortisol to surgical stress, we have studied the effect of naloxone on these hormones in otherwise normal subjects of both sexes undergoing cholecystectomy for gallstones. In 24 subjects (12 males and 12 females), premedication consisted of atropine sulfate (0.007 mg/kg BW); general anesthesia (30 min later) was induced by thiopental (7 mg/kg) and maintained constant by 1% ethrane in a 70%:30% nitrous oxide-oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…The present results show that plasma Prl increased while plasma LH decreased during stress, with the highest plasma Prl values and the lowest plasma LH values being detected in group V. It has been shown that stress stimulates Prl release (36)(37)(38) and inhibits LH release (39). Thus, the present results agree with previous reports and describe other markers (like isolation of the original group) of the stress condition in animals of group V.…”
Section: Discussionsupporting
confidence: 92%
“…The present results show that plasma Prl increased while plasma LH decreased during stress, with the highest plasma Prl values and the lowest plasma LH values being detected in group V. It has been shown that stress stimulates Prl release (36)(37)(38) and inhibits LH release (39). Thus, the present results agree with previous reports and describe other markers (like isolation of the original group) of the stress condition in animals of group V.…”
Section: Discussionsupporting
confidence: 92%
“…The methods used in the present study appeared to be the best possible approach, given that OGTT cannot be performed earlier, as it would be difficult to interpret due to fasting, to anesthesia, and to endocrine disturbances that last long after surgery [19,20]. It has also to be considered that changes of body weight with both BPD and LGB were quite reduced from the biological point of view.…”
Section: Discussionmentioning
confidence: 99%
“…The pathways mediating stress-related prolactin release are unclear but opioid peptides, in particular b-endorphins, play a role. 7 In contrast, melanocyte-stimulating hormone (MSH) appears to inhibit stress-induced increases.…”
Section: Regulation Of Prolactin Secretionmentioning
confidence: 99%